Identyfikacja i ocena skoordynowanych efektów koncentracji horyzontalnych w prawie Unii Europejskiej - Kociubiński, Jakub (Kwartalnik Prawa Publicznego, 2014)
Certain market structures are conductive to tacit coordination due to existence of sustainable mechanism of coordination. Such mechanism exists primarily on tight-knit oligopolistic markets. Post-merger situation where undertakings are able to behave in a parallel manner and derive benefits from their collective power is described as coordinated effects. It goes without saying that these effects are generally atypical in case of horizontal mergers as in this situation main anti-competitive effects are caused by the increase of market power of the single undertaking. However analysis of coordinated effects plays an increasingly important role in modern merger control analysis. This paper provides and analysis of criteria of assessment of coordinated effects and its relations with other concepts of collusive behavior regulated in EU Competition Law.